Пустыня - наш союзник: [роман] / Сергей Зверев - Зверев Сергей Иванович (Битва за Пальмиру, 2017)
Экземпляры: Ф. 1 (20190703) / Инвентарный номер: 47065 / Цена: 107.00 / Сис.шифр: Р 2 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6